Pengaruh Pembelajaran Inkuiri dan Kooperatif terhadap Hasil Belajar Kognitif Biologi pada Siswa SMA Berkemampuan Atas dan Bawah - Handoko Santoso, (Jurnal Penelitian Pendidikan Matematika dan Sains, 2008)
The infulence of inquiry and cooperative teaching on the  biology cognitive achievement of high and low ability student of Senior High School. The purpose of this research is to know the influence of biology teaching through inquiry integrated with cooperative towards the students cognitive achievement. This research addresses the role of inquiry and cooperative learning strategy as well as these interactions towards the increase of the cognitive achievement. Quasi experimental research of Pretest-postest nonequivalent control group design with factorial design 2x2x2 were implemented on the odd semester in academic years of 2006/2007  on X grade student of the state SMA in Metro City Lampung. The  research sample consists of 96 students, comprising of student from high and low academic abilities. To examine hypothesis, it is used Anacova technique and continued by LSD test. There was a difference on the cognitive achieve¬ment between students who learn by inquiry level 1 with student who learn by inquiry level 2, between students who learn by STAD cooperative  with student who learn by TPS, and between students who have high academic ability and students who have low academic ability. There is no effect of interaction between inquiry with cooperative, inquiry with students academic ability, cooperative with students academic ability, inquiry with cooperative and students academic ability towards the cognitive achievement